Phenomenological Enquiry Into Corporate Social Responsibility - Muzhar Javed (SEISENSE Journal of Management, 2018)
The notion of Corporate Social Responsibility (CSR) seems appealing amidst unprecedented corporate affluence and power vis-a-vis abject socio-economic and deteriorating environmental conditions. An increasing number of corporations have started exploiting social responsibility as insurance strategy against government intervention, media reporting and consumer reaction to irresponsible corporate behaviour. Analyzing retrospectively, current Social Responsibility Practices are far away from letter and spirit. This article aims to present critique of concept and practice of CSR. This phenomenological study, analyzing corporate practices, explores the ulterior motives precipitating corporations espouse CSR and finds that Social Responsibility is not social, it is economic phenomenon. The proposed model of CSR can make it social, sustainable and provide much-needed impetus to practice.